Rhizobial genetic and genomic resources for sustainable agriculture - Kohlmeier, M.G.; O'Hara, G.W.; Ramsay, Joshua; Terpolilli, J.J. (2024)
Rhizobia are a diverse group of α-and β-proteobacteria that boost soil fertility by forming a nitrogen-fixing symbiosis with legumes, which is why legumes are grown in rotation with cereals in agriculture. Rhizobia that naturally populate Australian soils are largely incompatible with exotic agricultural legumes, therefore, compatible strains have been imported from all over the world for use as inoculants. An amalgamated collection of these strains, called the International Legume Inoculant Genebank (ILIG), has been established at Murdoch University, to provide a centralised strain storage facility and support rhizobial research and inoculant development (see http://ilig.murdoch.edu.au). The ILIG contains 11,558 strains representing 96 bacterial species from 778 legume species collected from >1200 locations across 100 countries. New and sometimes inefficient rhizobia evolve in the field following legume inoculation, through horizontal symbiosis gene transfer from inoculants to soil bacteria. To provide a benchmark to monitor and assess the impact of this evolution, all commercial Australian inoculant strains were genome sequenced and these data made available (PRJNA783123, see https://www.ncbi.nlm.nih.gov/bioproject/PRJNA783123/). These data, and the further sequencing of the >11,000 historical strains in the ILIG, will increase our understanding of rhizobial evolution and diversity and provide the backbone for efforts to safeguard Australia's legume inoculation program.